2019
DOI: 10.1155/2019/7064319
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Ribosome Biogenesis Partly Induced p53-Dependent Aortic Medial Smooth Muscle Cell Apoptosis and Oxidative Stress

Abstract: Ribosome biogenesis is a crucial biological process related to cell proliferation, redox balance, and muscle contractility. Aortic smooth muscle cells (ASMCs) show inhibition of proliferation and apoptosis, along with high levels of oxidative stress in aortic dissection (AD). Theoretically, ribosome biogenesis should be enhanced in the ASMCs at its proliferative state but suppressed during apoptosis and oxidative stress. However, the exact status and role of ribosome biogenesis in AD are unknown. We therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
(57 reference statements)
1
14
1
Order By: Relevance
“…The immunofluorescence revealed that p53-positive cells in the media and neointimal significantly increased after BOP1 knockdown in the ligated mouse carotid artery, compared with the LV-SCR group ( Figure 2(j) ). Our previous study depicted that overexpression of BOP1 attenuated ROS production and cell apoptosis under serum-free and hypoxic conditions of HVSMCs in a p53-dependent way [ 13 ]. We therefore detected 8-hydroxy-2-deoxyguanosine (8-OHdG), a biomarker indicated the DNA damage induced by ROS, in the ligated carotid artery.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The immunofluorescence revealed that p53-positive cells in the media and neointimal significantly increased after BOP1 knockdown in the ligated mouse carotid artery, compared with the LV-SCR group ( Figure 2(j) ). Our previous study depicted that overexpression of BOP1 attenuated ROS production and cell apoptosis under serum-free and hypoxic conditions of HVSMCs in a p53-dependent way [ 13 ]. We therefore detected 8-hydroxy-2-deoxyguanosine (8-OHdG), a biomarker indicated the DNA damage induced by ROS, in the ligated carotid artery.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study revealed that the BOP1 knockdown may induce AMD through the upregulation of p53 [ 13 ]. As BOP1 is highly conserved in mammalian cells, and ribosome biogenesis also plays critical functions within normal cells, we tested the local intervention approach to avoid system side effects, in line with the practice of the clinical stent system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations